PENGARUH PERSEPSI HARGA, PROMOSI DAN KUALITAS PRODUK TERHADAP LOYALITAS KONSUMEN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL PEMEDIASI : STUDI EMPIRIS PADA KONSUMEN MCDONALD’S - Mutia Nadhira; Christina Dewi Wulandari (Gapenas Publisher, 2022)
The first McDonald's was founded in 1940 by brothers Dick and Mac McDonald, but was later purchased by Ray Kroc. They introduced the “Speedee Service System” in 1948, which later became the basic principle of modern fast-food restaurants. The purpose of this study was to analyze the effect of perceived price, promotion and product quality simultaneously and partially on consumer satisfaction. And looking for the largest independent variable on consumer satisfaction. The analysis method in this study uses quantitative primary data, the test stages carried out are: validity test, reliability test, normality test, heteroscedasticity test, multicollinearity test, path analysis, F test and T test. The data used in this study using a questionnaire instrrumen and valid data collected as many as 100 respondents. The submission tool used is SPSS version 26 software.Perceptions of price, promotion and product quality simultaneously affect satisfaction. The independent variables that partially affect satisfaction are the perception of price and product quality. These three variables have an effect on increasing purchasing decisions. Both of these variables have an effect on increasing customer satisfaction. Consumer satisfaction has an effect on loyalty where the higher the level of consumer satisfaction, the higher consumer loyalty. Product quality is the variable that has the strongest influence on consumer satisfaction